Anomalous ULF Emissions and Their Possible Association with the Strong Earthquakes in Sumatra, Indonesia, during 2007-2012 - Suaidi Ahadi; Nanang Tyasbudi Puspito; Gunawan Ibrahim; Sarmoko Saroso; Kiyohumi Yumoto; M. Muzli (Journal of Mathematical and Fundamental Sciences, 2015)
Eleven strong Sumatran earthquakes, with their epicenter less than 550 km away from the Kototabang (KTB) geomagnetic station (2007-2012), were studied to examine the occurrence of anomalous ultra-low frequency emissions (ULF-EM). Anomalous ULF signals, possibly associated with the earthquake's precursors, were determined by the Welch ratio SZ/SH at 0.06 Hz at the KTB station. These ULF anomalies were then compared with geomagnetic data observed from two reference stations in Darwin and Davao, to prevent misinterpretation of global geomagnetic disturbances as precursors. This study aims to analyze the relationship between earthquake magnitude and hypocenter radius, and seismic index against lead time during ULF-EM anomalies. We used the polarization ratio Welch method in terms of power spectrum density to evaluate the geomagnetic data by overlapping windows and applying fast Fourier transform (FFT). The results showed anomalous variations in onset and lead time, determined using the standard deviation controlling the SZ/SH power pattern. Our positive correlation between lead time of ULF emission and earthquake magnitude as well as between lead time and seismic index. It shows a negative correlation between hypocenter distances to KTB station against lead time.